3D reconstruction and histopathological analyses on murine corporal body. (9th February 2021) - Hashimoto, Daiki; Kajimoto, Mizuki; Ueda, Yuko; Hyuga, Taiju; Fujimoto, Kota; Inoue, Saaya; Suzuki, Kentaro; Kataoka, Tomoya; Kimura, Kazunori; Yamada, Gen
Abstract: Purpose: Erectile dysfunction (ED) is one of the increasing diseases with aging society. The basis of ED derived from local penile abnormality is poorly understood because of the complex three‐dimensional (3D) distribution of sinusoids in corpus cavernosum (CC). Understanding the 3D histological structure of penis is thus necessary. Analyses on the status of regulatory signals for such abnormality are also performed. Methods: To analyze the 3D structure of sinusoid, 3D reconstruction from serial sections of murine CC were performed. Histological analyses between young (2 months old) and aged (14 months old) CC were performed. As for chondrogenic signaling status of aged CC, SOX9 and RBPJK staining was examined. Results: Sinusoids prominently developed in the outer regions of CC adjacent to tunica albuginea. Aged CC samples contained ectopic chondrocytes in such regions. Associating with the appearance of chondrocytes, the expression of SOX9, chondrogenic regulator, was upregulated. The expression of RBPJK, one of the Notch signal regulators, was downregulated in the aged CC. Conclusions: Prominent sinusoids distribute in the outer region of CC which may possess important roles for erection. A possibility of ectopic chondrogenesis induced by alteration of SOX9/Notch signaling with aging is indicated.